Southern Gondwanan fungi associated with Nothofagaceae in Patagonia - Truong, Camille (2018)
Current understanding of fungal biodiversity is particularly limited in South America, yet global studies have identified many unique fungal lineages that are present in the Southern Hemisphere but absent from other regions. The ectomycorrhizal tree family Nothofagaceae is one striking example of vicariance associated with the final breakup of Southern Gondwana (part of the supercontinent that included South America, Antarctica and Australia) and the onset of Antarctic glaciation at theEocene/Oligocene boundary (ca. 32 mya). However, conflicting evidence suggests that long-distance dispersal or migration has continued long after the fragmentation of Southern Gondwana. As expectedfrom previous studies, we detected strong biogeographic connections between South America and Australasia within many ectomycorrhizal fungal lineages collected in our biodiversity assessment of the Patagonian region (Chile and Argentina). We traced the most recent common ancestors of several southern temperate lineages of Basidiomycota and Ascomycota using dated phylogenies built fromnuclear ribosomal loci ITS and LSU as well as RPB2 and EF1-alpha markers. We tested alternative hypotheses of vicariance or long distance-dispersal while taking into account the spore dispersalabilities, responses to disturbance, and whether taxa are early or late successional in Nothofagaceae forests. We also tested whether taxa with sequestrate fruiting bodies are more likely to have a restricted distribution and show evidence of a Southern Gondwanan origin. Our global approach using basidiomycete and ascomycete fungi with various life-history strategies will highlight common patternsfor ectomycorrhizal fungi in the Patagonian region.